Adding fish oil to whey protein, leucine, and carbohydrate over a six-week supplementation period attenuates muscle soreness following eccentric exercise in competitive soccer players - Philpott, J. D.; Donnelly, C.; Walshe, I. H.; MacKinley, E. E.; Dick, J.; Galloway, S. D. R.; Tipton, K. D.; Witard, O. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
Soccer players often experience eccentric exercise-induced muscle damage given the physical demands of soccer match-play. Since long chain n-3 polyunsaturated fatty acids (n-3PUFA) enhance muscle sensitivity to protein supplementation, dietary supplementation with a combination of fish oil-derived n-3PUFA, protein, and carbohydrate may promote exercise recovery. This study examined the influence of adding n-3PUFA to a whey protein, leucine, and carbohydrate containing beverage over a six-week supplementation period on physiological markers of recovery measured over three days following eccentric exercise. Competitive soccer players were assigned to one of three conditions (2 × 200 mL): a fish oil supplement beverage (FO; n = 10) that contained n-3PUFA (1100 mg DHA/EPA—approximately 550 mg DHA, 550 mg EPA), whey protein (15 g), leucine (1.8 g), and carbohydrate (20 g); a protein supplement beverage (PRO; n = 10) that contained whey protein (15 g), leucine (1.8 g), and carbohydrate (20 g); and a carbohydrate supplement beverage (CHO; n = 10) that contained carbohydrate (24 g). Eccentric exercise consisted of unilateral knee extension/flexion contractions on both legs separately. Maximal force production was impaired by 22% during the 72-hour recovery period following eccentric exercise (p < 0.05). Muscle soreness, expressed as area under the curve (AUC) during 72-hour recovery, was less in FO (1948 ± 1091 mm × 72 h) than PRO (4640 ± 2654 mm × 72 h, p < 0.05) and CHO (4495 ± 1853 mm × 72 h, p = 0.10). Blood concentrations of creatine kinase, expressed as AUC, were ~60% lower in FO compared to CHO (p?<?0.05) and tended to be lower (~39%, p?=?0.07) than PRO. No differences in muscle function, soccer performance, or blood c-reactive protein concentrations were observed between groups. In conclusion, the addition of n-3PUFA to a beverage containing whey protein, leucine, and carbohydrate ameliorates the increase in muscle soreness and blood concentrations of creatine kinase following eccentric exercise in competitive soccer players.